Surgeons reaching satisfying outcomes without surgery: nasal dorsum skin cancer recurrence treated with electrochemotherapy. Issue 7 (August 2020) - Pichi, Barbara; Moretto, Silvia; Petruzzi, Gerardo; Zocchi, Jacopo; Mazzola, Francesco; Manciocco, Valentina; Marchesi, Paolo; Pellini, Raul
Abstract : Cutaneous squamous cell carcinoma of the head and neck district are generally treated with surgery. Surgery is the standard treatment in early stages and local advanced tumors, followed by adjuvant therapy, radiation or concurrent chemoradiation therapy. Local recurrence treatment depends on previous therapies, though radical surgery is often the first choice at the expense of anatomy preservation. We present the case of a patient with cutaneous squamous cell carcinoma of the nasal dorsum which relapsed after surgery and radiation therapy. The patient refused radical surgery and electrochemotherapy under general anesthesia was administered. After 6 months from treatment, the patient showed a complete clinical response. Electrochemotherapy could be considered as an alternative to surgery in small lesion when other approaches are refused.